Penerapan Probabilitas dalam Sistem Skoring untuk Evaluasi Kelayakan Beasiswa Mahasiswa Prodi Matematika Universitas Negeri Medan Tahun 2022 - Arnah Ritonga; Ellys Rebecca Simanjuntak; Keisya Amelia Putri; Nafasa Zahri; Mhd. Fachrizal; Alya Dwi Lestari; Arief Rachman (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study aims to apply the concept of probability in the assessment system to assess students' eligibility to receive scholarships. By applying a probabilistic approach, especially Bayes' Theorem, this study develops a more objective and data-based evaluation method. The method used is a quantitative approach with probabilistic analysis, allowing the calculation of students' chances of getting scholarships based on factors such as Cumulative Achievement Index (IPK) and Single Tuition Fee (UKT). The data analyzed includes primary data from students applying for scholarships as well as secondary data from historical records of previous scholarship acceptances. The results of the study show that GPA plays a significant role in increasing the chances of receiving a scholarship, where students with higher GPAs are more likely to be accepted. Conversely, students with high UKT tend to have lower chances, indicating that financial conditions are also a major factor in selection. This probability-based approach increases transparency and fairness in the selection system and reduces subjectivity in decision making. This study confirms that a probability-based scoring system can be a fairer and more accurate solution in assessing the eligibility of scholarship recipients. It is hoped that the results of this study can be a reference for educational institutions in developing a more data-based and objective selection system.